AISLAMIENTO DE ESCHERICHIA COLI PRODUCTORA DE TOXINA SHIGA (STEC) EN HECES DE GANADO Y DETECCIÓN DE FACTORES DE VIRULENCIA ASOCIADOS CON SU PATOGÉNESIS - Edwin Quiguanás-Guarín (Asociación Colombiana de Infectología, 2021)
Objective: To isolate STEC in stool samples from cattle in Ulloa, Valle del Cauca, and to detect virulence factors associated with its pathogenesis. Materials and methods: We took 21 samples from cattle, which were taken directly from the rectum of the animal using swabs. The samples were processed until obtaining pure colonies and evaluated for the presence of the stx1, stx2, eae, saa and hlyA genes by PCR. Afterward, the cytotoxic effect of positive samples were evaluated on Vero cells (ATCC-CCL- 81.4). Results: We observed that from the 21 stools samples, 12 presented bacteria with one or both stx genes. A total of 106 isolates of STEC were obtained and differences among each other were observed regarding the presence and absence of the virulence genes, obtaining five combinations of genes. We found that 48 isolates presented only stx2 gene and 58 presented both the stx1 and stx2 gene. Regarding the other virulence genes, the hlyA gene was detected in 44 isolates and the saa gene was detected in 57 isolates. Conclusions: All the STEC supernatants showed cytotoxic activity on Vero cells, while in its absence the cells formed monolayer after 48 h of incubation. This work is the first report in Colombia that provides information about the presence of STEC in stool cattle, virulence genes and its potential cytotoxic effect in native strains.